Inverse electromagnetic scattering models for sea ice - Golden, Kenneth M.; Borup, D.; Cheney, M.; Cherkaeva, E.; Dawson, M.S.; Ding, K-H; Fung, A.K.; Isaacson, D.; Johnson, S.A.; Jordan, A.K.; Kong, J.A.; Kwok, R.; Nghiem, S.V.; Onstott, R.G.; Sylvester, J.; Winebrenner, D. P.; Zabel, I. H. H. (Institute of Electrical and Electronics Engineers (IEEE), 1998)
Journal Article Inverse scattering algorithms for reconstructing the physical properties of sea ice from scattered electromagnetic field data are presented. The development of these algorithms has advanced the theory of remote sensing, particularly in the microwave region, and has the potential to form the basis for a new generation of techniques for recovering sea ice properties, such as ice thickness, a parameter of geophysical and climatological importance. Moreover, the analysis underlying the algorithms has led to significant advances in the mathematical theory of inverse problems.